A shared leadership framework based on boundary spanners in megaprojects. Issue 5 (16th February 2021) - Cao, Tingting; Locatelli, Giorgio; Smith, Nigel; Zhang, Lianying
Abstract : Purpose: Megaprojects present an intricated pattern of leadership activities, which evolve over their planning and delivery and comprises several stakeholders. A framework is useful to navigate this complexity; it allows to identify and cluster the key elements. This paper aims to introduce a novel framework based on boundary spanners to describe the structural pattern of shared leadership in megaprojects. Design/methodology/approach: A systematic literature review about boundary spanning and shared leadership is used to identify and cluster the key elements of shared leadership in megaprojects. The systematic literature review provides a rich theoretical background to develop the novel shared leadership framework based on boundary spanners. Findings: There are three key dimensions characterizing shared leadership topology in megaprojects: stakeholders, boundary spanning leadership roles and project phases. The novel framework shows how project leadership dynamically transfers among different stakeholders, showing the importance of shared leadership as a leadership paradigm in megaprojects. Research limitations/implications: The novel framework epitomizes shared leadership in megaprojects by exploring its antecedents with social network metrics. This paper stresses that shared leadership is the envisaged form of leadership in megaprojects. By modeling complex project leadership in a simple, yet effective way, the framework fosters critical thinking for future research. The modeling introduced by this framework would also benefit practitioners in charge of megaprojects. Originality/value: The paper moves the project leadership research to the network-level by taking boundary spanners as shared leadership roles in megaprojects. It shows how shared leadership is a valuable management tool for planning and delivery megaprojects.